Habitat choice of the common periwinkle Littorina littorea depending on infection status and seasonality - Friederike Gronwald; Claudia Bommarito; Dakeishla M Díaz-Morales; Alessandro Manfrin; Cindy Martinez Reyes; Milen Nachev; Bernd Sures; Florian Weinberger (PANGAEA, 2025)
Littorina littorea were collected from the habitat, screened for infection and marked before being released back into the environment. After 24 hours they were recollected and the habitat in which they were found was recorded. Their infection status was then checked by dissection.
In: Gronwald, F et al. (2025): The diet contribution and habitat selection of the common periwinkle Littorina littorea depending on infection with parasites and seasonality [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.974526